Geochemistry and fluid circulation at the Tenorio volcanic complex (Costa Rica) - Vaselli, Orlando (2013)
The present work reports the geochemical results gathered from thermal and cold water and discharges, mainly located in the eastern part of the volcanic area of Tenorio